The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fneur.2019.00096
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Low Frequency Repetitive Transcranial Magnetic Stimulation and Motor Imagery on Upper Extremity Motor Recovery Following Stroke

Abstract: Objective: To investigate the effects of low frequency transcranial magnetic stimulation (LF-rTMS) combined with motor imagery (MI) on upper limb motor function during stroke rehabilitation. Background: Hemiplegic upper extremity activity obstacle is a common movement disorder after stroke. Compared with a single intervention, sequential protocol or combination of several techniques has been proven to be better for alleviating motor function disorder. Non-invasive neuromodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 44 publications
1
29
0
1
Order By: Relevance
“…Neurorehabilitation has been proposed and used for the treatment of motor paralysis in stroke, and its effect has been verified (10)(11)(12)(13)(14). One of the treatment methods, the NovEl intervention Using Repetitive transcranial magnetic stimulation and Occupational therapy (NEURO), facilitates peripheral muscle movement by controlling the excitability of the motor cortices by repetitive transcranial magnetic stimulation (rTMS).…”
Section: Introductionmentioning
confidence: 99%
“…Neurorehabilitation has been proposed and used for the treatment of motor paralysis in stroke, and its effect has been verified (10)(11)(12)(13)(14). One of the treatment methods, the NovEl intervention Using Repetitive transcranial magnetic stimulation and Occupational therapy (NEURO), facilitates peripheral muscle movement by controlling the excitability of the motor cortices by repetitive transcranial magnetic stimulation (rTMS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined if the combination of 1 Hz TMS is able to affect the upper extremity in patients with postischemic stroke [33]. It is suggested that intensive motor training combined with TMS is able to improve the WMFT log performance time from 3.23 (1.70-4.07) to 2.51 (1.36-3.86) and the total score of UEFMA from 48 to 51 (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) in patients with mild to moderate stroke [13]. The motor function showed significant differences between TMS with the rehabilitation program and TMS on the 7th day of upper extremity postischemic stroke (Table 3).…”
Section: Results and Dissectionmentioning
confidence: 99%
“…The first finding is that rTMS can potentially reverse SM-induced weight loss in rats and improve muscle atrophy, however the changes in body weight may have been caused by modeling effects on feeding and excretion in rats ( Pan et al, 2019 ). As for sport-related hindlimb muscles, why did SM cause the Sol to atrophy, but not the MG?…”
Section: Discussionmentioning
confidence: 99%